Technological pedagogical content knowledge (TPACK) in teaching 21st century skills in the 21st century classroom / Hidayu Shafie, Faizah Abd Majid and Izaham Shah Ismail. - Shafie, Hidayu; Abd Majid, Faizah; Ismail, Izaham Shah (Universiti Teknologi MARA, 2019)
This conceptual paper explores the concept of technological pedagogical content knowledge (TPACK) in relation to the teaching of 21st century skills with a purpose of establishing a relationship between them. Due to the advancement and development of industrial revolution and technology, the education scenario also changes towards 21st century education, whereby more focus is given on the use of technology and 21st century skills. The teachers’ roles change, and they are required to not only teach the core subject matters, but they also have to teach and train the students with the 21st century skills. However, not all teachers are well-trained on how to teach those skills to the students, especially when they also have to integrate technology in their teaching as well. Therefore, it is crucial to investigate whether the teachers understand and know how to teach the 21st century skills while integrating technology at the same time. Based on this needs, this paper will discuss the teachers’ knowledge, understanding and application of the TPACK framework by Koehler et al. (2006) and how will this framework affect their teaching of 21st century skills in the classroom. The 21st century skills framework suggested by the Malaysian Ministry of Education called the 4C1V (communication, collaboration, critical thinking, creative thinking and values and ethics) which is based on the P21 framework is included in the conceptual framework of this study, along with the TPACK framework. This study will attempt to establish a relationship between these two frameworks through a quantitative study, and the findings from this study would contribute to the knowledge on what aspects or skills that teachers will need to improve in order to teach the 21st century skills to the students.